2020
DOI: 10.1016/j.celrep.2020.107614
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson’s Disease Protein LRRK2 Interacts with the GARP Complex to Promote Retrograde Transport to the trans-Golgi Network

Abstract: Highlights d The Parkinson's disease kinase LRRK2 interacts with the GARP complex at the TGN d LRRK2 stabilizes the binding of GARP to the t-SNARE Syntaxin-6 d LRRK2 regulates retrograde and anterograde transport in a kinase-dependent manner d Depletion of GARP intensifies neurodegeneration in C. elegans expressing G2019S-LRRK2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 70 publications
1
63
0
Order By: Relevance
“…LRRK2 knockout in rodent models LRRK2 is expressed in many tissues and cell types, with highest expression in lung, kidney, and immune cells and relatively low expression in the brain [88]. LRRK2 knockout mice and rats have discolored kidneys with lysosomal pathology that progresses with age [88][89][90][91][92][93][94]. For example, LRRK2 knockout leads to the formation of large vacuoles, the accumulation of lipofuscin granules, and formation of high-molecular weight ubiquitin-positive protein aggregates in the kidneys [88][89][90][91][92][93].…”
Section: Lrrk2 Deletion Disrupts the Endolysosomal Pathwaymentioning
confidence: 99%
See 4 more Smart Citations
“…LRRK2 knockout in rodent models LRRK2 is expressed in many tissues and cell types, with highest expression in lung, kidney, and immune cells and relatively low expression in the brain [88]. LRRK2 knockout mice and rats have discolored kidneys with lysosomal pathology that progresses with age [88][89][90][91][92][93][94]. For example, LRRK2 knockout leads to the formation of large vacuoles, the accumulation of lipofuscin granules, and formation of high-molecular weight ubiquitin-positive protein aggregates in the kidneys [88][89][90][91][92][93].…”
Section: Lrrk2 Deletion Disrupts the Endolysosomal Pathwaymentioning
confidence: 99%
“…The Rab29-LRRK2 pathway is also important for retrograde trafficking as knockout or dominantnegative Rab29 expression disrupts retrograde trafficking of M6PR, Sortilin and Furin from endosomes and lysosomes to the TGN [79,128]. Beilina et al has recently reported a novel interaction between LRRK2, Rab29 and the Golgi-associated retrograde protein (GARP) complex [94]. Specifically, LRRK2 and Rab29 interact with the GARP complex component VPS52 at the TGN.…”
Section: Lrrk2 and The Golgi Networkmentioning
confidence: 99%
See 3 more Smart Citations